Prevalence of Osteoporosis in Postmenopausal Type 2 Diabetic Women with Diabetic Peripheral Neuropathy - Subhash Kumar; Surya K. Singh; Saurabh Singh (Indian Journal of Endocrinology and Metabolism)
Introduction: There is evidence that diabetic peripheral neuropathy (DPN) is associated with increased risk for fractures in type 2 diabetes mellitus (T2DM). We planned a study to assess the prevalence of osteoporosis and vertebral fractures (VFs) in postmenopausal type 2 diabetic women aged 40–60 years with DPN and to find out their relationship with severity of DPN. Methods: This cross-sectional observational study included sixty-two postmenopausal type 2 diabetic women of age 40–60 years, out of them thirty-two were with DPN and thirty were without DPN. The presence of DPN was established based on history and clinical examination. Plain X-ray spine and bone mineral density (BMD) measured by dual-energy X-ray absorptiometry were used to assess vertebral fracture and osteoporosis, respectively. Results: The prevalence of osteoporosis in women with DPN was 68.75% at lumbar spine (LS) and 18.75% at femoral neck (FN), and osteoporosis at LS was statistically significant compared to those without DPN (P = 0.002). On subgroup analysis in women with DPN, the osteoporosis at LS showed significant association with lower body mass index (BMI) (P = 0.015), but not with severity of DPN. The prevalence of VFs in women with DPN was 6.25% with no statistical significance in comparison with other group. Conclusion: Our study revealed high prevalence of osteoporosis at LS in postmenopausal type 2 diabetics with DPN. VFs are most common consequence of osteoporosis, although we could not find significant prevalence of VFs in women with DPN that may be due to small sample size and cross-sectional study design.